2011
DOI: 10.1016/j.molimm.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Bright plays a role in marginal zone B lymphocyte development and autoantibody production

Abstract: Previous data suggested that constitutive expression of the transcription factor Bright (B cell regulator of immunoglobulin heavy chain transcription), normally tightly regulated during B cell differentiation, was associated with autoantibody production. Here we show that constitutive Bright expression results in skewing of mature B lineage subpopulations toward marginal zone cells at the expense of the follicular subpopulation. C57Bl/6 transgenic mice constitutively expressing Bright in B lineage cells genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 71 publications
1
28
0
Order By: Relevance
“…6) are alternative pre-pro B cells associated with autoreactive immunoglobulin repertoires. However, over-expression of ARID3a in B lineage cells in transgenic mice resulted in autoreactive antibody production (19, 28), and the humanized mouse model data presented herein also suggest that autoantibodies may be preferentially generated in mice reconstituted with ARID3a H versus ARID3a L cells (Table 1). Using a gating strategy characterized by Griffin et al (41, 42), we identified small numbers of putative human B1-like B cells in the spleens of our chimeric mice.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…6) are alternative pre-pro B cells associated with autoreactive immunoglobulin repertoires. However, over-expression of ARID3a in B lineage cells in transgenic mice resulted in autoreactive antibody production (19, 28), and the humanized mouse model data presented herein also suggest that autoantibodies may be preferentially generated in mice reconstituted with ARID3a H versus ARID3a L cells (Table 1). Using a gating strategy characterized by Griffin et al (41, 42), we identified small numbers of putative human B1-like B cells in the spleens of our chimeric mice.…”
Section: Discussionmentioning
confidence: 61%
“…ARID3a expression in mouse B cells was associated with autoantibody production (19). Therefore, we examined sera from each of the recipient mice for the presence of antinuclear antibodies (ANAs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] Recently, Oldham et al demonstrated that BRIGHT transgenic mice exhibit defects in B-cell maturation and that constitutive Bright expression predisposes B cells to the development of marginal zone differentiation. 25 BTK, which was found to be mutated in one patient here, has a crucial role in B-cell development, marginal zone differentiation and signalling through the BCR/Bruton's tyrosine kinase (BTK) pathway. 26 Interestingly, BTK associates with ARID3A to bind DNA.…”
Section: Discussionmentioning
confidence: 89%
“…Human ARID3a and the mouse orthologue, Bright ( B cell r egulator of i mmuno g lobulin h eavy chain t ranscription) bind to sequences 5′ of some IgH promoters and to the matrix attachment regions (MARs) that flank the intronic IgH enhancer (59), where, in association with Bruton’s tyrosine kinase (Btk) and the transcription factor II-I (TFII-I), they upregulate IgH transcription in activated B cells (10, 11). Additional studies with transgenic mice that over-expressed Bright/ARID3a indicated roles for this protein in marginal zone versus follicular B cell fate decisions, and as a contributing factor for production of autoantibodies (12, 13). …”
Section: Introductionmentioning
confidence: 99%